Transcriptomic and metabolomic analyses reveal the potential mechanism of waterlogging resistance in cotton (Gossypium hirsutum L.) - Owusu, Anane Gideon; Lv, Yin-Ping; Liu, Man; Wu, Yong; Li, Cheng-Lin; Guo, Ning; Li, Da-Hui; Gao, Jun-Shan (Frontiers in Plant Science, 2023)
Cotton (Gossypium hirsutum L.) is susceptible to long-term waterlogging stress; however, the genomic information of cotton response mechanisms towards long days of waterlogging is quite elusive. Here, we compared the transcriptome genes and metabolite expression level changes in cotton roots after 10 and 20 days of waterlogging stress treatment. Numerous adventurous roots and hypertrophic lenticels on cotton stem and roots were induced. Transcriptome analysis revealed 101,599 differentially expressed genes in cotton roots with higher gene expression after 20 days of stress. Reactive oxygen respiratory (ROS) generating gene, antioxidant enzyme genes, and transcription factor genes (AP2, MYB, WRKY, and bZIP) were highly responsive to waterlogging stress. Phenylpropanoid biosynthesis pathway significantly induced at both transcript and levels of studies. At metabolite level of the study, the accumulation of sinapyl alcohol, L-glutamic acid, galactaric acid, glucose 1-phosphate, L-valine, L-asparagine, and melibiose metabolites were significantly responsive in both cotton accessions under waterlogging stress. In addition, the metabolite accumulation results were significantly correlated with the transcript-seq profile. This investigation enabled us to identify genes for targeted genetic engineering to improve waterlogging stress resistance in cotton genotypes and to further understand abiotic stress regulatory mechanisms on stress crosstalk in cotton at the transcript and metabolic levels.